2022
DOI: 10.1021/acs.orglett.2c02993
|View full text |Cite
|
Sign up to set email alerts
|

Aza-PNA: Engineering E-Rotamer Selectivity Directed by Intramolecular H-bonding

Abstract: The replacement of α(CH 2 ) by NH in monomers of standard aeg PNA and its homologue β-ala PNA leads to respective aza-PNA monomers (1 and 2) in which the N α H can form either an 8membered H-bonded ring with folding of the backbone (DMSO and water) or a 5-membered N α H�αCO (water) to stabilize E-type rotamers. Such aza-PNA oligomers with exclusive E rotamers and intraresidue backbone H-bonding can modulate its DNA/RNA binding and assembling properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Those E/Z-rotamers influenced the orientation preference of PNA in the formation of the complex. The same research group also reported aza-PNA bearing a nitrogen atom instead of a carbon atom at the α-position (Figure 9, 36) [93]. Interestingly, the aza-PNA monomer assumed the E-form via an eight-membered hydrogen-bonded ring with backbone folding.…”
Section: Modification Of the Peptic Nucleic Acid Backbonementioning
confidence: 83%
“…Those E/Z-rotamers influenced the orientation preference of PNA in the formation of the complex. The same research group also reported aza-PNA bearing a nitrogen atom instead of a carbon atom at the α-position (Figure 9, 36) [93]. Interestingly, the aza-PNA monomer assumed the E-form via an eight-membered hydrogen-bonded ring with backbone folding.…”
Section: Modification Of the Peptic Nucleic Acid Backbonementioning
confidence: 83%